The Impact of Internal Performance and Macroeconomic Conditions on Profitability in Indonesian Banking From 2015-2017 - I Wayan Sunarya (University of Merdeka Malang, 2018)
The purpose of this study is to analyze and measure the effect of internal performance and macroeconomics conditions on profitability in Indonesian banking (conventional and syariah bank) from 2015-2017. This research uses Granger of Causality and Vector Autoregressive (VAR)/Vector Error Correction Model (VECM) as a data analysis tool. The conclutions of this research are: 1) For conventional banks: the factors that have a positive influence to profitability (ROA) are BI Rate, NPL, inflation, and loan to deposit ratio; 2) For Islamic banks: the factors that have a positive influence to profitabilty (ROA) are exchange rate and inflation https://doi.org/10.26905/jmdk.v6i2.2374